Effect of long-term operation on steels of main gas pipeline: Structural and mechanical degradation - Maruschak P. O. Pavel Orestovich; Panin S. V. Sergey Viktorovich; Chausov M. G.; Bishchak R. T. Roman Teodorovich; Polyvana U. V. (2018, 2018)
Title screen